Röntgen der Brust- und Lendenwirbelsäule bei verletzten Kindern und Jugendlichen: Aufkommen, Frakturrate und Therapiekonsequenz = X-ray of the thoracic and lumbar spine in injured children and adolescents : incidence, fracture rates and therapeutic consequences - Ruffing, Thomas; Winkler, Hartmut; Muhm, Markus Joachim (Der Unfallchirurg, 2018)
IntroductionUsually, conventional radiographs are appropriate for injuries in the region of the thoracic and lumbar spine (TLS) in children and adolescents. The aim of our study was to determine the incidence of trauma-associated radiographic findings in this anatomical region and to present the therapeutic consequences.Material and methodsIn a retrospective cohort study (2007-2015) of a level 1 trauma center all children and adolescents (0-17 years) with a TLS-trauma, in which conventional radiographs were performed anteroposterior and lateral as the initial imaging modality, were included.ResultsIn 396 children and adolescents conventional radiographs were performed, but only 5.6 % suffered a fracture. Conventional radiographs were performed in 188 cases of the thoracic spine, in 43 cases in the thoracolumbar junction and in 255 cases in the lumbar spine. On average, children and adolescents with fractures were 12.5 (5-17) years old. Fractures were classified as 38.7 % A1.1, 51.6 % A1.2, and 9.7 % were fractures of the transverse process. B and C fractures could not be detected. Of all fractures, 80 % were found in the mid-thoracic spine and the thoracolumbar junction. All fractures could be treated conservatively.ConclusionWith 5.6 % TLS-injuries in children and adolescents, the study revealed a low fracture rate in a highly radiosensitive region. With regard to an expected stable fracture morphology and the absent surgical consequences, the indication for emergency radiographs should be provided restrictively.
Gesehen am 20.09.2019
Online publiziert: 28. Oktober 2016